2021
DOI: 10.1016/j.semcancer.2019.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Tumor antigens heterogeneity and immune response-targeting neoantigens in breast cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 139 publications
(181 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, actionable co-alterations in PIK3CA and DNA repair genes might lead to the activation of the human leukocyte antigen (HLA) molecules due to increased TMB and subsequent neoantigens production, particularly in the metastatic setting [ 13 , 45 , 46 ]. This subset of patients represents a possible target for immunotherapy with ICB [ 47 ].
Fig.
…”
Section: Mismatch Repair Alterations In Hr+ Breast Cancermentioning
confidence: 99%
“…Furthermore, actionable co-alterations in PIK3CA and DNA repair genes might lead to the activation of the human leukocyte antigen (HLA) molecules due to increased TMB and subsequent neoantigens production, particularly in the metastatic setting [ 13 , 45 , 46 ]. This subset of patients represents a possible target for immunotherapy with ICB [ 47 ].
Fig.
…”
Section: Mismatch Repair Alterations In Hr+ Breast Cancermentioning
confidence: 99%
“…In the early years, the therapeutic effect was witnessed in tumors with strong immunogenicity, especially melanoma [7]. But now, cancer biotherapy research has been spread into breast cancer [8], lung cancer [9] and liver cancer [10]. Meanwhile, anti-neovascularization drugs, monoclonal antibodies, cancer vaccines, gene therapy drugs and immunomodulators have been used clinically and been studied in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown evidence of an association between immune activity and selective pressures 8,34,51,55,59 , others have claimed that there is a lack of evidence to prove this relationship 16 . Given that several studies have applied dN/dS as a metric of selection in cancer and in normal tissue 7,8,[60][61][62][63] , we aimed to prove the use of hypothesis, a recent study of longitudinal recurrence of metastasis reported a more aggressive phenotype in metastatic deposits that had higher levels of immune-selection 55 . However, whether tumor cells growing in immunecompetent tissues are more likely to colonize new niches and how long it takes those tumor cells to readapt or to find a novel escape mechanism, as has been previously observed in mice models 31,64 , remains a challenging question.…”
Section: Discussionmentioning
confidence: 99%